2019
DOI: 10.3390/met10010059
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Behavior and Experiments on a Light Alloy Seamless Tube via a Tandem Skew Rolling Process

Abstract: As a process for producing seamless tubes, the tandem skew rolling (TSR) process was proposed. In order to study deformation characteristics and mechanism on tubes obtained by the TSR process, a numerical simulation of the process was analyzed using Deform-3D software. Simulation results demonstrated the distribution of stress, strain, velocity, and temperature of a seamless tube in the stable stage during the TSR process. Actual experiments of carbon steel 1045, high strength steel 42CrMo, and magnesium alloy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Via comparing the exerted force in the simulation with the average of 53.199 kN and the experimental results with an average of 48 kN and comparing the force fluctuations during the process, the accuracy of the FEM simulation results can be confirmed with the use of experimental results at the first 5 s of the process. 8 After mathematical modelling and carrying out simulation via FEM software, the extracted results are shown from all four assumed specimens within the process. In Supplementary table 2, the comparison has been illustrated between the geometrical parameters of the manufactured tube in all assumed types of RTP process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Via comparing the exerted force in the simulation with the average of 53.199 kN and the experimental results with an average of 48 kN and comparing the force fluctuations during the process, the accuracy of the FEM simulation results can be confirmed with the use of experimental results at the first 5 s of the process. 8 After mathematical modelling and carrying out simulation via FEM software, the extracted results are shown from all four assumed specimens within the process. In Supplementary table 2, the comparison has been illustrated between the geometrical parameters of the manufactured tube in all assumed types of RTP process.…”
Section: Resultsmentioning
confidence: 99%
“…This point can express the condition of the mandrel is more critical than other components of the piercing system. Mao et al 7,8 developed the rolling process through numerical theoretical and experimental methods. The upper bound solution has been implemented as the theoretical section to calculate the load force was calculated.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the increased isotropy of the deformed and annealed aluminium sheet is a product of the texture heterogeneity and reduced volume fractions of the separate texture components. Mao et al [8] proposed tandem skew rolling (TSR) for the production of seamless tubes. In order to study the deformation characteristics and mechanism on tubes obtained by the TSR process, a numerical simulation of the process was analysed using Deform-3D software.…”
Section: Contributionsmentioning
confidence: 99%
“…Another aspect that enhances the model accuracy is the correlation of strain. Mao et al [15] combined a numerical study of a Tandem Skew Rolling Process with experimental tests to analyse strain parameters such as the wall thickness of the tube.…”
Section: Introductionmentioning
confidence: 99%